Morphological Awareness and Vocabulary Knowledge - Zrig, Ahmed (International Journal of English Literature and Social Sciences (IJELS), 2020)
This study examined the relationship between the types of vocabulary knowledge (receptive and productive) and morphological awareness in an EFL context. The participants in this study were 60 fourth year secondary school Arts students in Ain Drahem, Tunisia. Students were grouped into two groups (control/ experimental) in order to check the effectiveness of teaching morphology on vocabulary knowledge. Vocabulary size was tested using adapted versions of vocabulary tests, namely Nation’s (2001) Vocabulary Levels Test as a receptive measure of vocabulary size and Laufer and Nation’s (1999) productive version of the Vocabulary Levels Test. The tests were modified by increasing the total number of test items to make them more representative of the 2000 and 3000-word frequency levels. Students’ morphological awareness was measured by the Morphological Awareness Test with its four subsets (roots, derivational morphemes, compounds and inflectional morphemes).The VLT results showed that students’ receptive size was larger than their productive size. Results revealed also that students performed better at the 2000-word frequency level than at the 3000-word level. Besides, the informants’ scores were high on the overall morphological awareness task, and the best performance was on inflectional morphemes for both groups. As predicted, morphological awareness was positively related to both receptive and productive vocabulary.